ممارسة العلاقات العامة الرقمية في المؤسسات الجامعية دراسة تحليلية للصفحة الرسمية لجامعة محمد الشريف مساعدية - سوق أهراس- على الفيس بوك- - جلايلية ايمان; لبناقرية آمال (My University, 2022)
Study summary: This study aims to identify how digital public relations are practiced at Mohamed Sherif Mosadeya University, through its analysis of its official page on Facebook, where it tried to answer the following main questionHow does Muhammad Sharif University practice digital public relations assistance through its official page on Facebook ? Answering the sub-questions:  What are the most prominent forms of presentation that Muhammad Sharif Mosadeya University uses to publish its digital content on its official Facebook page?  What is the nature of the topics that Muhammad Sharif University publishes on its Facebook page ?  What are the forms of public interaction with the digital content of the official page of Muhammad Sharif University Musadia on Facebook ?  What are the forms of interaction of the institution with its audience through its official page on Facebook ?  Where the study used the descriptive approach, in addition to using the content analysis tool and the interview .  We relied on the non-probability sample (intentional), then the study started from the systematic approach to organization .  :The study reached the most important results  The university's page employs various media in displaying its digital content and relies more on text supported by an image .  Mohamed Sherif Mosadeya University does not rely on documenting its digital content on its official page with the blue tick .  The university's Facebook page deliberately publishes its various topics and activities to introduce the university and improve its image. Most of the university's page publications witnessed the public's interaction with positive comments related to the content of the publication, and this contributed to its participation on various pages, which increases the definition of the university's page and increases the number of its followers . --------------------------------------------- ملخص الدراسة : تهدف هذه الدراسة للتعرف على كيفية ممارسة العالقات العامة الرقمية في جامعة محمد شريف مساعدية، من خالل تحليلها لصفحتها الرسمية على الفيس بوك، حيث حاولت اإلجابة على التساؤل الرئيسي التالي: - كيف تمارس جامعة محمد شريف مساعدية العالقات العامة الرقمية من خالل صفحتها الرسمية على الفيس بوك ؟ واإلجابة على األسئلة الفرعية :  ما هي أبرز أشكال العرض التي تستخدمها جامعة محمد شريف مساعدية في نشر محتواها الرقمي على صفحتها الرسمية عبر الفايسبوك؟  ما طبيعة المواضيع التي تنشرها جامعة محمد الشريف مساعدية عبر صفحتها الفيس بوك ؟  ما هي أشكال تفاعل الجمهور مع المحتوى الرقمي للصفحة الرسمية لجامعة محمد الشريف مساعدية على الفيس بوك؟  ما هي أشكال تفاعل المؤسسة مع جمهورها من خالل صفحتها الرسمية على الفيس بوك؟ .  حيث استخدمت الدراسة المنهج الوصفي ،باإلضافة إلى استخدام أداة تحليل المحتوى و المقابلة .  واعتمدنا على العينة الغير احتمالية ) القصدية( ،ثم انطلقت الدراسة من المقاربة النسقية للتنظيم. وتوصلت الدراسة إلى نتائج أهمها :  توظف صفحة الجامعة الوسائط المتعددة بشكل متفاوت في عرض محتواها الرقمي ويعتمد بشكل أكبر على النص المدعم بصورة .  ال تعتمد جامعة محمد شريف مساعدية على توثيق محتواها الرقمي صفحتها الرسمية بالعالمة الزرقاء.  تعمد صفحة الجامعة على موقع الفايسبوك في نشر مختلف مواضيعها و نشاطاتها للتعريف بالجامعة و تحسين صورتها. ولقد شهدت معظم منشورات صفحة الجامعة تفاعل الجمهور بالتعليقات االيجابية المتعلقة بمحتوى المنشور، وهذا ما ساهم في مشاركتها عبر مختلف الصفحات مما يزيد في التعريف بصفحة الجامعة ورفع من عدد متابعيها.
Keywords: العلاقات العامة، العلاقات العامة الرقمية ، مواقع التواصل الاجتماعي ،المؤسسات الجامعية.